2008
DOI: 10.1017/s0950268808000939
|View full text |Cite
|
Sign up to set email alerts
|

Type C bovine botulism outbreak due to carcass contaminated non-acidified silage

Abstract: The first reported bovine botulism outbreak in Finland is described. Nine out of 90 cattle on a dairy farm died after being fed non-acidified silage contaminated by animal carcasses. Type C botulinum neurotoxin gene was detected in one heifer by polymerase chain reaction (PCR) and the neurotoxin was detected by the mouse bioassay. Clostridium botulinum type C was isolated from liver samples. The isolated strain was identified with amplified fragment length polymorphism (AFLP) analysis as group III C. botulinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
3
34
0
4
Order By: Relevance
“…The symptoms observed in the affected buffaloes, including sudden death, sternal recumbency, inability to stand, and flaccid paralysis, were similar to those described in botulism outbreaks in ruminants, and the absence of macroscopic and microscopic pathological changes corroborated the results of previous studies, which reported the lack of major changes or the presence of mild changes (Senturk & Cihan 2007, Myllykoski et al 2009, Moreira et al 2014.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The symptoms observed in the affected buffaloes, including sudden death, sternal recumbency, inability to stand, and flaccid paralysis, were similar to those described in botulism outbreaks in ruminants, and the absence of macroscopic and microscopic pathological changes corroborated the results of previous studies, which reported the lack of major changes or the presence of mild changes (Senturk & Cihan 2007, Myllykoski et al 2009, Moreira et al 2014.…”
Section: Discussionsupporting
confidence: 88%
“…The difficulty to detect botulinum toxin in animal tissue samples using this technique has been reported in other studies and is justified by rapid degradation of the toxins, particularly type C toxin, by the ruminal microflora and the higher sensitivity of ruminants to BoNTs compared with mice, which are less sensitive in the bioassay (Kelch et al 2000, Myllykoski et al 2009, Bano et al 2015.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…2 It produces neurotoxin in environments that permit germination of the spores, such as canned food and silage. 3,4 The accessibility and dissemination potential of C. botulinum spores in combination with the high health impact on both humans and animals also make the bacterium a biological risk agent. 1 Botulism is usually caused by ingestion of preformed toxin, but there are also cases caused by toxicoinfection.…”
mentioning
confidence: 99%